Wood Anatomical Responses of European Beech to Elevation, Land Use Change, and Climate Variability in the Central Apennines, Italy - Miranda, Jose Carlos; Calderaro, Chiara; Cocozza, Claudia; Lasserre, Bruno; Tognetti, Roberto; von Arx, Georg (Frontiers in Plant Science, 2022)
European beech (Fagus sylvatica L.) is a widespread and economically important temperate tree species in Europe. The warmer temperatures and severe drought events expected in the future, especially in Mediterranean areas, could affect the vitality and productivity of beech stands that have been intensively used in these areas in the past. Here, we aim to assess the wood anatomical responses of beech to environmental variability and silvicultural practices by investigating three beech stands along an elevational gradient (1,200 to 1,950 m a.s.l.) in the Apennines (Italy). Therefore, we quantified several anatomical traits of the xylem vessels related to tree hydraulics from five trees per stand and investigated variability between and within tree rings. Our results suggest generally limited trait plasticity, with higher plasticity of mean vessel lumen area and theoretical hydraulic conductivity, while maximum vessel size and mean hydraulic diameter were less plastic, likely because of the stronger determination by tree height. High-elevation trees were hydraulically more limited than trees at a mid and lower elevation as indicated by the more conservative anatomical configuration, i.e., comparatively smaller vessels and a 50% tighter trait coordination. Cessation of coppicing resulted in a hydraulically safer anatomy with comparatively smaller vessels at the most intensively used site (1,200 m), triggered by increased water demand due to an increase in canopy density, and thus, an increase in stand transpiration. Furthermore, maximum vessel size at the beginning showed different climate sensitivity compared to the rest of the tree ring, while intra-ring anatomical profiles showed little difference between normal and the 5 years with the highest and lowest mean temperature and precipitation. Overall, this study highlights the challenges to separate the externally induced medium- to longer-term responses from ontogenetically determined patterns. We, therefore, call for more comprehensive studies to further explore and verify the plasticity of wood anatomical traits in European beech in response to short- to long-term environmental fluctuations to gain a mechanistic understanding useful for sustainable forest ecosystems.